VI. MARITAL CONFLICT, VAGAL REGULATION, AND CHILDREN'S SLEEP: A LONGITUDINAL INVESTIGATION. Issue 1 (March 2015) - El‐Sheikh, Mona; Hinnant, J. Benjamin; Erath, Stephen A.
ABSTRACT: We examined longitudinal relations between adult interpartner conflict (referred to as marital conflict) and children's subsequent sleep minutes and quality assessed objectively via actigraphy, and tested parasympathetic nervous system (PNS) activity indexed through respiratory sinus arrhythmia reactivity (RSA‐R) and initial sleep as moderators of predictive associations. At Wave 1 (W1), children (85 boys, 75 girls) with a mean age of 9.43 years ( SD  = .69) reported on marital conflict, and their sleep was assessed with actigraphs for seven nights. Sleep minutes, sleep efficiency, sleep activity, and number of long wake episodes were derived. RSA‐R was measured in response to a lab challenge. Sleep parameters were assessed again 1 year later at Wave 2 (W2; mean age = 10.39; SD  = .64). Analyses consistently revealed 3‐way interactions among W1 marital conflict, sleep, and RSA‐R as predictors of W2 sleep parameters. Sleep was stable among children with more sleep minutes and better sleep quality at W1 or low exposure to marital conflict at W1. Illustrating conditional risk, marital conflict predicted increased sleep problems (reduced sleep minutes, worse sleep quality) at W2 among children with poorer sleep at W1 in conjunction with less apt physiological regulation (i.e., lower levels of RSA‐R or less vagal withdrawal) at W1. Findings build on the scant literature and underscore the importance of simultaneous consideration of bioregulatory systems (PNS and initial sleep in this study) in conjunction with family processes in the prediction of children's later sleep parameters.